PEC 65/2023 and the overlooked relationship between the Central Bank and the National Treasury - Naves Deus Dornelas, Larissa (Brazilian Keynesian Review, 2024)
Dated November 27, 2023, Proposed Amendment to the Constitution No. 65 of 2023 provides for a change in the legal regime of the Brazilian Central Bank, which, from an autarchy, would become a public company, enjoying total financial autonomy. Despite the importance of the issue, the text justifying PEC nº65/23 does not present the necessary technical rigor about the suggested new institutionality of the Central Bank, either in legal terms or in economic terms. The aim of this paper is to help clarify the implications of this proposal, especially in view of the relationship between the Brazilian Central Bank and the National Treasury. Despite the idea of bringing Brazil into line with (some) international practices, PEC nº65/23 ignores the Monetary Authority's own state functions, as well as specific elements of the Brazilian economy in this area: its public debt market merged with the money market and the extremely high weight of repo operations in managing the liquidity of its currency.